TECHNICAL GUIDANCE ON THE DEVELOPMENT OF BNSP LEARNING METHODOLOGY AND CERTIFICATION FOR EDUCATORS IN SERANG CITY - Jaka Wijaya Kusuma; Bambang Dwi Suseno; Ahmad Mukhlis; Wahyu Wiguna; Isnaini Mahuda; Ulfi Jefri; Ranny Meilisa (International Journal of Engagement and Empowerment, 2021)
Currently, the use of Copyright Media is now a necessity, and there is already tension in the process in the educational process. Both school level and university level. Media, let alone the process of transfer of knowledge and the center of attention. Media is vital Until And Up Education, then in education is significantly skill every Educator. BNSP collaborates with Bina Bangsa University to improve manufacturing skills and skills and media skills. Media Skills And How to Skill generation skills and technical guidance on media development Academic Media and Skills Skills. This activity was created with BNSP and LSP FIT as speakers of bimtek activities with media design materials and study methods with power points. This activity is a satisfactory response because educators become intelligent media and Methods Until Copyright Work By Way of The Process of Becoming Learners. This activity is carried out with certification from BNSP so that if this BIMTEK Participant passes will get an official certificate from BNSP. With this Bimtek activity, leaders can improve education in Serang City